Care During Pregnancy, Childbirth, Postpartum, and Human Milk Feeding for Individuals Who Identify as LGBTQ+. Issue 1 (January 2021) - Griggs, Kellie M.; Waddill, Colette B.; Bice, April; Ward, Natalie
Abstract : Abstract: The growing number of families that include members of sexual and/or gender minority (SGM) groups requires perinatal nurses to know how to provide respectful and affirming care to all people, including this population. Approximately 19% of adults who are members of SGM groups are raising 3 million children, with many hoping to become pregnant, foster, use surrogacy, or adopt in the future. Based on current literature, many nurses are not prepared to meet the clinical needs of patients who are members of SGM groups in the maternity setting. Likewise, patients and families of SGM groups often perceive that nurses are uncomfortable with providing care and are not always satisfied with their care. To meet these needs, it is important that nurses use strategies focused on promoting respectful, affirming care, reducing negative experiences, and eliminating marginalizing language and practices. Nurses must incorporate a holistic care focus for patients who are members of SGM minority groups that includes standardized strategic education; development of Lesbian, Gay, Bisexual, Transgender, Queer, Questioning, or Plus (LGBTQ+) affirming and inclusive policies, practices, and language; flexibility, personal reflection of self-bias; and creating an environment of individualized compassionate care. Abstract : Individuals who identify as LGBTQ+ need and deserve respectful, affirming, compassionate care during pregnancy, labor, birth, postpartum, and human milk feeding. A review is offered to promote high quality nursing care for this population. Details of providing human milk including inducing lactation and co-lactating are covered in detail.